2005
DOI: 10.3171/jns.2005.103.1.0087
|View full text |Cite
|
Sign up to set email alerts
|

Novel laser tissue-soldering technique for dural reconstruction

Abstract: Fascia-dura mater soldering using the CO2 laser is feasible and may support CSF pressure up to six times higher than normal intracranial pressure. Findings of this study may provide a basis for the development of new tools for dural reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…Other thermal interaction applications are tissue welding [7] and soldering [8,9]. The parameters that affect the thermal interaction were investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Other thermal interaction applications are tissue welding [7] and soldering [8,9]. The parameters that affect the thermal interaction were investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sutures pose a risk of complications, including infection [1], induced astigmatism [2], erosion [3], foreign body sensation, irritation of the cornea and conjunctiva from exposed knots and corneal edema, neovascularization [4], and leakage [5]. Soldering techniques have been studied for more than 30 years [6,7] as an alternative to sutures for tissue bonding [8][9][10][11][12], including sclero-corneal and corneal cuts [13,14]. Pini et al [14] were the first to apply laser welding in clinical transplantation of the cornea over a decade ago.…”
Section: Introductionmentioning
confidence: 99%
“…The material is applied to the approximated edges of the surgical cut, and the laser beam heats the solder and the underlying cut edges [9,11]. Several experimental studies have shown that laser soldering is efficient for bonding different types of tissues [8,10,[12][13][14], including the cornea [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used on vascular tissue, in the urinary tract, and on cornea tissue. [21][22][23][24][25][26] Soldering creates an immediate watertight closure. LTS results in less inflammation with faster inflammatory recovery than suturing procedures.…”
mentioning
confidence: 99%